The UK Equity Release Market: Views from the Regulatory Authorities, Product Providers and Advisors - Tripti Sharma; Declan French; Donal G. McKillop (Queen's University Belfast, Queen's Management School, 2020)
This study investigates the factors driving the development of the UK equity release market. The results of a thematic review of semi-structured interviews with industry stakeholders (comprising senior representatives of product providers, advice providers and regulators) suggest that the attractiveness of the equity market for insurance companies (the main funders of the market), has diminished following a decline in annuity business and complications around the capital maturity matching requirements under Solvency II. Product costs (interest charges, and the cost of financial advice) are high. Trust in the market has improved, but remains fragile. Increased entry into the market by recognised brand names, (such as the traditional mortgage providers) would increase competition, reduce costs and promote trust. The risk of reputational damage limits the appeal of the market to new entrants. The no negative equity guarantee, a cost in terms of lower than otherwise loan-to-value ratios, promotes demand by way of the protection it affords to customers and their beneficiaries. Equity release is unsuitable for funding long-term care and policymakers advocating it as such damage the market.
Keywords: G21; G22; J14; 330; Equity release; Transaction costs; Trust; Solvency II